Social constructionist and essentialist beliefs about gender and race. (February 2023) - Schudson, Zach C.; Gelman, Susan A.
Social constructionist beliefs posit that sociocultural forces shape power-stratified social categories, whereas essentialist beliefs posit that social categories are defined by an immutable, natural essence shared by category members. Across three studies, we developed and validated the Social Constructionist and Essentialist Beliefs Scale (SCEBS) to assess the latent structure of ontological beliefs about two social categories: gender and race. In Study 1 ( N = 598), we found a three-factor structure for SCEBS-Gender and SCEBS-Race, consisting of Social Constructionism, Essentialism, and Realism. In Study 2a ( N = 300), we examined factor structure stability and criterion-related validity. We found incremental validity of SCEBS, and social constructionist beliefs particularly, for predicting modern sexism and symbolic racism beyond extant, essentialism-focused measures. In Study 2b ( N = 218), we established 4-week test–retest reliability of SCEBS. Our research demonstrates the value of assessing both social constructionist and essentialist beliefs in the study of prejudice.